The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13102-021-00292-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate and population health: a narrative review of the translational potential of existing laboratory studies

Abstract: Background Dietary inorganic nitrate (NO3−) is a polyatomic ion, which is present in large quantities in green leafy vegetables and beetroot, and has attracted considerable attention in recent years as a potential health-promoting dietary compound. Numerous small, well-controlled laboratory studies have reported beneficial health effects of inorganic NO3− consumption on blood pressure, endothelial function, cerebrovascular blood flow, cognitive function, and exercise performance. Translating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 211 publications
(314 reference statements)
0
17
2
Order By: Relevance
“…Health status: The expert panel agreed that chronic dietary nitrate supplementation was ergogenic in healthy individuals, but did not reach consensus for acute supplementation being ergogenic in this population. The expert panel also felt that there was insufficient evidence, or were unable to reach consensus, for acute or chronic dietary nitrate supplementation being ergogenic in clinical populations, which is consistent with the mixed findings reported in the current literature for these cohorts (for a review, see [ 71 ]). It is important to highlight that only 58% of the expert panel reported having experience of using dietary nitrate with clinical populations, compared with 100% of the panel having experience with healthy or sporting populations.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Health status: The expert panel agreed that chronic dietary nitrate supplementation was ergogenic in healthy individuals, but did not reach consensus for acute supplementation being ergogenic in this population. The expert panel also felt that there was insufficient evidence, or were unable to reach consensus, for acute or chronic dietary nitrate supplementation being ergogenic in clinical populations, which is consistent with the mixed findings reported in the current literature for these cohorts (for a review, see [ 71 ]). It is important to highlight that only 58% of the expert panel reported having experience of using dietary nitrate with clinical populations, compared with 100% of the panel having experience with healthy or sporting populations.…”
Section: Discussionmentioning
confidence: 79%
“…Although these changes in the oral microbiome composition occurred alongside marked increases in NO biomarkers, it is important to note that the net oral nitrite production is influenced by a complex interplay between various nitrate- and nitrite-reducing microorganisms in the oral cavity. The influence of chronic dietary nitrate consumption on nitrate-reduction capacity of the oral microbial community in response to acute nitrate ingestion, and the impact of potential changes in relation to health and exercise performance, requires further exploration [ 71 ]. One recent study has shown positive associations between oral nitrate-reducing capacity and markers of aerobic fitness [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary nitrate therefore has the mechanistic potential to influence brain functions; however, observational and clinical trials, overall, have contrasting results (19,49) . A meta-analysis conducted in 2018 exploring the effects of dietary nitrate supplementation on cognition and CBF (19) found a lack of evidence for the benefits of dietary nitrate on both outcomes.…”
Section: Dietary Nitrate and Brain Healthmentioning
confidence: 99%
“…During the last decade, there has been an increased interest in investigating the health aspects of dietary nitrate supplementation (aimed to increase NO bioactivity) with a particular focus on cardiovascular regulation and exercise performance [3,4,11,12]. With this in mind, we previously hypothesized that dietary nitrate supplementation may be of benefit in boosting the activity of the nitrate-nitrite-NO pathway, thus restoring NO bioactivity in adult HD patients [10].…”
Section: Introductionmentioning
confidence: 99%